2022
DOI: 10.3389/fmicb.2022.861025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Replacing Alfalfa Hay With Native Grass Hay in Pelleted Total Mixed Ration on Physicochemical Parameters, Fatty Acid Profile, and Rumen Microbiota in Lamb

Abstract: This study aimed to investigate the effects of replacing alfalfa with native grass on growth performance, meat quality, and rumen microbiota of lambs. Forty-five 6-month-old Ujimqin lambs with live body weight (BW) of 29.50 ± 0.26 kg were used for the experiment, and the lambs were assigned to three diet treatments (three pens per treatment and five lambs per pen) with 30 square meters per pen in semi-open housing based on similar BW. The lambs have received 30% alfalfa (HA, high alfalfa percentage group), 20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Indeed, the different substrates of the diet affect the growth of rumen microbiota (Maslowski and Mackay, 2011;Li et al, 2012;Kasparovska et al, 2016). Previous reports found that Prevotella_1, Rikenellaceae_RC9_gut_group, F082_unclassfied, and Succinivibrio were the genera of the core-microbiome (Du et al, 2022;Zhou et al, 2022). In the present study, these genera were influenced by the physical forms and chemical compositions, whereas the stability of the most abundant bacteria can reflect the presence of the genus-core microbiome (Henderson et al, 2015;Lin T. et al, 2021).…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Indeed, the different substrates of the diet affect the growth of rumen microbiota (Maslowski and Mackay, 2011;Li et al, 2012;Kasparovska et al, 2016). Previous reports found that Prevotella_1, Rikenellaceae_RC9_gut_group, F082_unclassfied, and Succinivibrio were the genera of the core-microbiome (Du et al, 2022;Zhou et al, 2022). In the present study, these genera were influenced by the physical forms and chemical compositions, whereas the stability of the most abundant bacteria can reflect the presence of the genus-core microbiome (Henderson et al, 2015;Lin T. et al, 2021).…”
Section: Discussionmentioning
confidence: 45%
“…At intervals of 7 days, the initial BW and the final BW were also recorded. The growth performance was analyzed based on the difference between the final BW and the initial BW (Du et al, 2022). At the end of the experiment, all of the lambs were transferred and slaughtered at a commercial slaughterhouse (Xilin Hot, China).…”
Section: Feed Intake Growth Performance and Rumen Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicated that feeding different ratios of AF in the AF–SS silage-based diets had an effect on the microbiota composition of lambs. Du et al [ 41 ] reported that the composition of the bacterial community of lambs fed diets with 10%, 20%, 30% AF inclusion was distinctly separated according to PCoA analysis, which indicated that different bacteria prefer different nutrients and ruminal environments.…”
Section: Discussionmentioning
confidence: 99%
“…The common and unique OTUs was used to construct the Venn diagram by R (version 1.6.2). The alpha diversity for these samples were used the Chao1 value and Shannon index to evaluate richness and diversity [17][18][19][20], and Good's coverage were calculated through QIIME software. Principal coordinates analysis (PCoA) was conducted on OTU level by R (version 3.3.1) software based on weighted UniFrac distances.…”
Section: Bioinformatics and Statistical Analysismentioning
confidence: 99%